The Evolution of Anatomic Anterior Cruciate Ligament Reconstruction - Getgood, Alan (Bentham Open, 2012)
Anterior cruciate ligament reconstruction has evolved significantly since the early 1900’s, back when an emphasis was placed on repair and not reconstruction. Over the past century, the technique has evolved from intra-articular non anatomic reconstruction, to extra articular reconstruction, back to intra articular (performed arthroscopically), to now, the advent of anatomic insertion site restoration. This review will aim to illustrate the changes that have occurred, describing the rational for this process, based upon anatomical, radiological, biomechanical and clinical studies, all of which have aimed to improve patient function following ACL injury.